2013
DOI: 10.1016/j.actamat.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic transformation of deformed austenite at temperatures above the Ae3

Abstract: The dynamic transformation behavior of deformed austenite was studied in four steels of increasing carbon contents that had been deformed over the temperature range 743 -917°C. These experiments were carried out in torsion under an atmosphere of argon and 5% H 2 and the experimental temperatures were above the ortho and para-equilibrium Ae 3 temperatures of the steels.Strains of 0.15 -5 were applied at strain rates of 0.4 -4.5 s -1 . The experimental parameters were varied in order to determine the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 23 publications
12
98
0
Order By: Relevance
“…The absence of martensite between the plates in steel 1 is consistent with the thermodynamic analysis of Ref. 4), in which it is shown that C is only rejected during plate formation when the C level exceeds about 0.1%. Transmission electron microscopy 5) and atom probe tomography 15) revealed the presence of fine carbides on dislocations and at grain boundaries; however, due to their fine scale they could not be detected using the EBSD techniques employed in the present work.…”
Section: Microstructuresupporting
confidence: 72%
See 3 more Smart Citations
“…The absence of martensite between the plates in steel 1 is consistent with the thermodynamic analysis of Ref. 4), in which it is shown that C is only rejected during plate formation when the C level exceeds about 0.1%. Transmission electron microscopy 5) and atom probe tomography 15) revealed the presence of fine carbides on dislocations and at grain boundaries; however, due to their fine scale they could not be detected using the EBSD techniques employed in the present work.…”
Section: Microstructuresupporting
confidence: 72%
“…(4), that the strain is at a maximum at the surface of the specimen, while it is zero along the axis. The amount of dynamic transformation is therefore expected to be at a maximum at the outer surface and to decrease to zero along the radius.…”
Section: Microscopic Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first minimum identifies the start of dynamic transformation (DT), while the second specifies that of dynamic recrystallization (DRX). As shown in earlier studies using microstructural analyses, 6,7,21) the critical strain for DT is always lower than that for DRX.…”
Section: Critical Strainsmentioning
confidence: 74%